Comparison between robotic natural orifice specimen extraction surgery and traditional laparoscopic low anterior resection for middle and low rectal cancer: A propensity score matching analysis. Issue 4 (2nd June 2021) - Feng, Qingyang; Ng, Simon S. M.; Zhang, Zhiyuan; Lin, Songbin; Niu, Zhengchuan; Wei, Ye; He, Guodong; Chang, Wenju; Zhu, Dexiang; Xu, Jianmin
Abstract: Background and Objectives: This study aimed to find the advantages of robotic natural orifice specimen extraction surgery (NOSES) for middle and low rectal cancer, compared with traditional laparoscopic low anterior resection (LAR). Methods: Patients receiving robotic NOSES or traditional laparoscopic LAR were retrospectively enrolled from 2013‐10 to 2019‐06, with middle and low rectal cancer, maximum diameter ≤ 5 cm, pT1–3 or ypT1–3 stage, no distant metastases. The baseline of the two groups was balanced using the propensity score matching method. Surgical quality, postoperative recovery, and long‐term oncological outcomes were compared. Results: Totally 137 eligible patients with robotic NOSES and 137 matched patients with traditional laparoscopic LAR were enrolled. Robotic NOSES had a significantly lower open conversion rate (0 vs. 4.4%, p = .030), less intraoperative hemorrhage (50 ml vs. 80 ml, p < .001) and longer distance from distal resection margin of low rectal cancer (1.5 cm vs. 1.0 cm, p = .030). Robotic NOSES significantly reduced the 30‐day postoperative complication rate of Clavien‐Dindo grade II or higher (17.5% vs. 31.4%, p = .008), promoted gastrointestinal and urinary function recovery, reduced postoperative pain and hospital stay (6.0 vs. 7.0 d, p = .022). The two groups were similar in long‐term survival. Conclusions: Compared with traditional laparoscopic LAR, robotic NOSES had significant advantages in improving surgical quality and promoting postoperative recovery.